Cloud computing : principles and paradigms - Buyya, Rajkumar, 1970-; Broberg, James; Gościński, Andrzej (Hoboken, N.J. : Wiley, 2011)
"The primary purpose of this book is to capture the state-of-the-art in Cloud Computing technologies and applications. The book will also aim to identify potential research directions and technologies that will facilitate creation a global market-place of cloud computing services supporting scientific, industrial, business, and consumer applications. We expect the book to serve as a reference for larger audience such as systems architects, practitioners, developers, new researchers and graduate level students. This area of research is relatively recent, and as such has no existing reference book that addresses it. This book will be a timely contribution to a field that is gaining considerable research interest, momentum, and is expected to be of increasing interest to commercial developers. The book is targeted for professional computer science developers and graduate students especially at Masters level. As Cloud Computing is recognized as one of the top five emerging technologies that will have a major impact on the quality of science and society over the next 20 years, its knowledge will help position our readers at the forefront of the field"--Provided by publisher.
"The primary purpose of this book is to capture the state-of-the-art in Cloud Computing technologies and applications. The book will also aim to identify potential research directions and technologies that will facilitate creation a global market-place of cloud computing services supporting scientific, industrial, business, and consumer applications. We expect the book to serve as a reference for larger audience such as systems architects, practitioners, developers, new researchers and graduate level students. This area of research is relatively recent, and as such has no existing reference book that addresses it"--Provided by publisher.
Introduction to cloud computing / William Voorsluys, James Broberg, and Rajkumar Buyya -- Migrating into a cloud / T.S. Mohan -- Enriching the 'integration as a service' paradigm for the cloud era / Pethuru Raj -- The enterprise cloud computing paradigm / Tariq Ellahi ... [et al.] -- Virtual machines provisioning and migration services / Mohamed El-Refaey -- On the management of virtual machines for cloud infrastructures / Ignacio M. Llorente ... [et al.] -- Enhancing cloud computing environments using a cluster as a service / Michael Brock and Andrzej Goscinski -- Secure distributed data storage in cloud computing / Yu Chen ... [et al.] -- Aneka - integration of private and public clouds / Christian Vecchiola ... [et al.] -- CometCloud: an automatic cloud engine / Hyunjoo Kim and Manish Parashar -- T-systems' cloud-based solutions for business applications / Michael Pauly -- Workflow engine for clouds / Suraj Pandey, Dileban Karunamoorthy, and Rajkumar Buyya -- Understanding scientific applications for cloud environments / Shantenu Jha ... [et al.] -- The MapReduce programming model and implementations / Hai Jin ... [et al.] -- An architecture for federated cloud computing / Benny Rochwerger ... [et al.] -- SLA management in cloud computing : a service provider's perspective / Sumit Bose ... [et al.] -- Performance prediction for HPC on clouds / Rocco Aversa ... [et al.] -- Best practices in architecting cloud applications in the AWS cloud / Jinesh Varia -- Massively multiplayer online game hosting on cloud resources / Vlad Nae, Radu Prodan, and Alexandru Iosup -- Building content delivery networks using clouds / James Broberg -- Resource cloud mashups / Lutz Schubert ... [et al.] -- Organizational readiness and change management in the cloud age / Robert Lam -- Data security in the cloud / Susan Morrow -- Legal issues in cloud computing / Janine Anthony Bowen -- Achieving production readiness for cloud services / Wai-Kit Cheah and Henry Kasim.
Includes bibliographical references and index.
Keywords: Cloud computing